Antimicrobial resistance and antimicrobial resistance genes in marine bacteria from salmon aquaculture and non‐aquaculture sites. (2nd April 2014) - Shah, Syed Q. A.; Cabello, Felipe C.; L'Abée‐Lund, Trine M.; Tomova, Alexandra; Godfrey, Henry P.; Buschmann, Alejandro H.; Sørum, Henning
Summary Antimicrobial resistance (AR) detected by disc diffusion and antimicrobial resistance genes detected by DNA hybridization and polymerase chain reaction with amplicon sequencing were studied in 124 marine bacterial isolates from a Chilean salmon aquaculture site and 76 from a site without aquaculture 8 km distant. Resistance to one or more antimicrobials was present in 81% of the isolates regardless of site. Resistance to tetracycline was most commonly encoded by tetA and tetG; to trimethoprim, by dfrA1, dfrA5 and dfrA12; to sulfamethizole, by sul1 and sul2; to amoxicillin, by blaTEM; and to streptomycin, by strA‐strB. Integron integrase intl1 was detected in 14 sul1‐positive isolates, associated with aad9 gene cassettes in two from the aquaculture site. intl2 Integrase was only detected in three dfrA1‐positive isolates from the aquaculture site and was not associated with gene cassettes in any. Of nine isolates tested for conjugation, two from the aquaculture site transferred AR determinants to Escherichia coli. High levels of AR in marine sediments from aquaculture and non‐aquaculture sites suggest that dispersion of the large amounts of antimicrobials used in Chilean salmon aquaculture has created selective pressure in areas of the marine environment far removed from the initial site of use of these agents.